Redes interorganizacionais horizontais como sistemas adaptativos complexos: um estudo em uma rede de supermercados do Sul de Minas Gerais. - Oliveira, Aline Lourenço de (2009)
The horizontal inter-organizational networks (HINs) have been studied under distinct scopes. Aiming to contributing to studies about them, this piece of work takes a different look at them as a starting point into understanding the uprising and development phenomenon of such organizational form. The precepts of Complex Adaptive Systems (CAS) along with those of co-evolution´s were used, as both approaches find their fundaments in the Theory of Complexity. One agrees to the notion that HINs show evidences of being CASs originated from a co-evolutional process and, as a CAS, the network itself would, as well, be in the middle of an evolutionary process. This means, research-wise, starting from the events that occurred before the establishment of the network, through its present conception and structure and following ahead into seeking to understand the system´s behavioral dynamics. The aim was to identify the basic characteristics of a complex adaptive system which are present in a horizontal inter-organizational network of supermarkets in the south of Minas Gerais. A qualitative case study was carried out, for that purpose, in the retail purchase network, named Ômega Network for study purposes. A theorical model was built as for the aim of the research, which ranges three dimensions: agent, system and auto-organization. For every dimension there are sub-dimensions which seek to evidencing the central elements of the theorical axes. It was verified that the network under study rose from the co-evolutional behavior of its members, thus generating a new system. The system, which is actually the network itself, features a formal structure set up to assure the system´s operability and an informal structure, which rose spontaneously from inter-personal relations. The Ômega Network shows, therefore, strong evidence of self-organized behavior. There is also that the network is in the process of co-evolution, which can be felt from the movement that the actors perform to monitor trends in the industry. Concluded that it was appropriate to adopt the paradigm of complexity to understand the phenomenon of development of HINs, is meant that this study has implications for understanding the competitiveness on the level of networks and the importance of learning and innovation in its development. This work also opens space for new studies of networks as organizational forms evolve in the new context of business.